2009
DOI: 10.1103/physreve.80.031143
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Langevin equations: Markovian and non-Markovian dynamics

Abstract: Non-Markovian stochastic Langevin-like equations of motion are compared to their corresponding Markovian (local) approximations. The validity of the local approximation for these equations, when contrasted with the fully nonlocal ones, is analyzed in detail. The conditions for when the equation in a local form can be considered a good approximation are then explicitly specified. We study both the cases of additive and multiplicative noises, including system-dependent dissipation terms, according to the fluctua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 23 publications
0
43
1
Order By: Relevance
“…It has been shown that the stationary probability distribution function (PDF) is independent of magnitudes of additive and multiplicative noises and of the relaxation time of colored noise [20][21][22]29], although the response to applied input depends on noise parameters [29]. This is in contrast with previous studies [30][31][32] which show that the stationary PDF of the Langevin model for the harmonic potential is Gaussian or non-Gaussian, depending on magnitudes of additive and multiplicative noises.…”
Section: Introductioncontrasting
confidence: 54%
See 4 more Smart Citations
“…It has been shown that the stationary probability distribution function (PDF) is independent of magnitudes of additive and multiplicative noises and of the relaxation time of colored noise [20][21][22]29], although the response to applied input depends on noise parameters [29]. This is in contrast with previous studies [30][31][32] which show that the stationary PDF of the Langevin model for the harmonic potential is Gaussian or non-Gaussian, depending on magnitudes of additive and multiplicative noises.…”
Section: Introductioncontrasting
confidence: 54%
“…We consider a system of a Brownian particle coupled to a bath consisting of N -body uncoupled oscillators, which is described by the generalized CL model [20][21][22]29],…”
Section: A Non-markovian Langevin Equationmentioning
confidence: 99%
See 3 more Smart Citations